The effects of World War II on economic and health outcomes across Europe - Iris Kesternich; Bettina Siflinger; James P. Smith; Joachim K. Winter (Institute for the Study of Labor (IZA), 2012)
In this paper, we investigate the long-run effects of World War II on socio-economic status (SES) and health of older individuals in Europe. Physical and psychological childhood events are important predictors for labor market and health outcomes in adult life, but studies that quantify these effects in large samples that cover entire diverse populations are still rare. We will analyze data from SHARELIFE, a retrospective survey conducted as part of the Survey on Health, Aging, and Retirement in Europe (SHARE) in 2009. This survey provides detailed data on events in childhood including those during the war as well as several measures of exposure to war shocks such as experience of dispossession, persecution, combat in local areas, and hunger periods for over 20,000 individuals in 13 European countries. We find that exposure to the war itself, and even more importantly to individual-level shocks caused by the war such as hunger periods, significantly predict old-age outcomes at older ages.
urn:nbn:de:101:1-201203145695
Keywords: I0; H0; 330; health; war; SES; Kriegsfolgen; Alte Menschen; Sozialer Status; Gesundheit; Europa